Feasibility of E-Comic Learning Media in the Making of Phase F Blouse Patterns - Luvita Nafisah; Wulansari Prasetyaningtyas (Jurnal Penelitian Pendidikan, 2026)
Vocational High Schools (SMK) have a strategic role in preparing students to be ready to compete in the world of work through mastery of technical skills and understanding of industry concepts. In the Fashion Skills Program, one of the important materials in the Preparation element of Fashion Making Preparation phase F is the creation of blouse patterns. Learning this material is generally rarely found in the form of E-comics. Therefore, this study aims to assess the feasibility of E-comic learning media in the material for making blouse pattern phase F. This study uses a quantitative descriptive method. The feasibility of E-comics is assessed by material experts and media experts using instruments that have been proven to be valid and reliable. The data was analyzed using a percentage descriptive technique to determine the level of media feasibility based on the criteria that had been set. The results showed that E-comics made blouse patterns obtained a feasibility percentage of 91.1% from material experts and 88.8% from media experts, which is included in the "Very Feasible" category.